RELATIONSHIPS BETWEEN SEED YIELD AND OTHER PLANT TRAITS IN DESI AND KABULI CHICKPEA (CICER ARIETINUM L.) PARENTS AND THEIR MUTANTS DEVELOPED THROUGH INDUCED MUTATIONS - T. M. Shah; B. M. Atta (Journal of Animal and Plant Sciences, 2013)
The correlations between seed yield and other plant traits of 79 genetically stable induced chickpea mutants of two desi (Pb2000 and C44), one kabuli (Pb-1) and one desi x kabuli introgression (CH40/91) were studied. At maturity seventeen different traits were measured in the replicated trial. The results indicated that yield was significantly correlated with primary branches, secondary branches, canopy width, pods per plant, hundred seed weight, biological yield and harvest index in all the four chickpea genotypes and their mutants. The results have suggested that in a chickpea breeding program aiming to break the yield barrier the selection criteria must include these traits for the development of improved germplasm and new cultivars.
Keywords: Induced mutants; chickpea; Correlation coefficient analysis; morphological characteristics; positive and negative correlations